Materials for a History of Hungarian Academic Orientalism: The Case of Gyula Germanus - Mestyan, Adam (Die Welt des Islams, 2014)
This article provides materials for an institutional history of academic Hungarian Orientalism through the life of Gyula Germanus (1884-1979). Using hitherto unexploited archives, this text explores his education, integration into academia, and career up to 1939. I argue that Germanus was an assimilated Hungarian of Jewish origin with a strong loyalty to the state. His two conversions – to Calvinism in 1909 and to Islam in 1930 – also transformed him from a minor Turkologist into a popularly acclaimed Arabist. This study demonstrates that academic Orientalism as a national science was a contested vehicle of social mobility in the Hungarian transition from an imperial to a nation-state setting.